Current and projected future risks of freshwater fish invasions in China. Issue 12 (19th September 2019) - Liu, Chunlong; Comte, Lise; Xian, Weiwei; Chen, Yifeng; Olden, Julian D.
Abstract : Biological invasions are a primary threat to global biodiversity, supporting mounting calls for the development of early‐warning systems to manage existing and emerging invaders. Here, we evaluated the geographical pattern of invasion risks of currently established and potentially emerging nonnative freshwater fishes in China by jointly considering the threats of introduction and establishment under climate change. Introduction threats were estimated according to proxies of human activities and propagule pressure for two primary pathways (aquaculture or ornamental). Establishment threats for 51 current and 64 potential invaders (based on whether having established or not self‐sustaining populations) were assessed using an ensemble of species distribution models under current (1960–1990) and future [2041–2060 (2050s) and 2061–2080 (2070s)] climate scenarios. Geographical patterns of invasion risk were then assessed by overlaying the threats of introduction and establishment for each species group both in present‐day and in the future. We found that eastern China displayed the highest threat of introduction. By contrast, southeastern and northwestern regions were identified as the most suitable for the establishment of both current and potential invaders. Under a changing climate, 83 out of 115 species displayed an increase in habitat suitability, resulting in an overall increase of 4.8% by 2050s and 7.1% by 2070s in the extent of suitable habitat for nonnative freshwater fishes. Taken together, invasion risk was found to be highest in southeastern China and lowest in the Tibet Plateau. Our research highlights the importance of assessing invasion risk by integrating the threats associated with the introduction and establishment stages. In particular, our findings revealed convergent patterns of invasion risk between current and potential nonnative freshwater fishes under climate change. Geographic patterns in hotspots of existing and emerging invasions provide critical insights to guide the allocation of resources to monitor and control existing and emerging invasions in China.